Can homicide detectives improve homicide clearance rates? - Braga, Anthony Allan (Crime & delinquency, 2018)
The available scientific evidence on the value of detectives in clearing crimes generally suggests that most crimes are solved through the random circumstances of crime scenes rather than special follow-up investigation. Other research, however, suggests that the work of criminal investigators can increase the likelihood that crimes might be cleared through arrest. After years of homicide clearance rates that were lower than the national average, the Boston Police Department engaged a problem-oriented policing approach to improve their post-homicide criminal investigation processes and practices. Our quasi-experimental statistical analyses suggest that the intervention significantly increased key investigative activities and improved Boston homicide clearance rates relative to existing homicide clearance trends in other Massachusetts and U.S. jurisdictions.